The tumor suppressor gene TP53 and colorectal cancer: A review - Agrawal, Sujan Narayan (Innovative Journal of Medical and Health Sciences, 2020)
TP53 is a gene and the p53 is its protein product. It is well known as a tumor suppressor gene, due to its inherent property of apoptosis and its role in the suppression of tumor formation. Its oncogenic property is due to p53 mutation. This oncogenic property is named “gain of oncogenic property”. The functions of p53 have been studied the world over, especially the oncogenic function. It is well known for its role to induce apoptosis, but now it is established that it is also a key player in cell cycle regulation. It controls and monitors the cell division, chromosomal segregation, and cellular senescence. Due to all these important cellular functions, this protein is labeled as the “guardian of the genome”. The p53 protein is a nuclear phosphoprotein. It is composed of 393 amino acids. The structural and functional domains are an N-terminal transactivation domain, a protein-rich regulatory domain, and a C-terminal domain involved in the regulation of DNA binding. The colorectal cancers (CRC) are a major cause of morbidity and mortality world over. This is the third most common cancer worldwide and the fourth most common cause of death. Although it is slow-growing cancer the five-year survival is low. It is a heterogeneous disease and is due to, a complex genetic and biochemical interplay. This review summarizes the functions of p53 and its role in CRC. Keywords: TP53, p53, colorectal cancers, CRC, Tumor suppressor gene, apoptosis, cellular senescence, guardian of the genome.